An Evaluation of Effects of the Advancement Via Individual Determination (Avid) Program in Osceola County, Florida. Issue 4 (October 2021) - Maddock, David R.; Torres, Leah C.
The School District of Osceola County, Florida, invests heavily in the Advancement Via Individual Determination (AVID) program, and as such, an evaluation of effects was conducted with a sample of 10 middle schools (12, 325 students) and 7 high schools (18, 886 students). Propensity matching was used to determine practical effects. Providing schoolwide AVID was correlated with higher school grades in the Florida accountability system, and students in the elective were found to have statistically significantly higher GPAs, higher learning gains scores, greater enrollment in acceleration, and a higher likelihood of receiving college scholarships.